ANTIBIOTICS RESIDUES IN MILK OF BAGHDAD AREA - H. Najim, Najim; F. Khazal, Kamel; H. Ali, Jalil (The Iraqi Journal of Veterinary Medicine, 1988)
Hazardous residues in milk are reviewed with a special emphasis upon antibiotic residues in cow's milk. In this study a survey involving 1700 milk samples from three collection centers (Al-Fadhilia, Abu Ghraib and Al- Taji Center) and the farm of the College of Agriculture, was carried out. Milk samples were collected within three months and tested for antibiotic residues using a microbiological assay by using Bacillus subtilus modified method of cylinder plate method. The percentage of positive samples out of 1700 milk samples collected from the three centers ranged from 8.6% to 9.4%.